1981
DOI: 10.1093/nar/9.11.2517
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the β-lactamase promoter of pBR322

Abstract: The beta-lactamase promoter of pBR322, derived from Tn3, has been characterized using several techniques. The transcription initiation site is located 35 base pairs from the translation initiation codon of beta-lactamase. The mRNA produced in vitro has a 5' pppGpA terminus. RNA polymerase bound at this start site protects a region from about -50 to +20 from DNase I cleavage using the footprinting technique. RNA polymerase binds rapidly to the beta-lactamase promoter. The half-time of association is less than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 38 publications
3
20
1
Order By: Relevance
“…Twenty-one of the 23 strains presenting a PL penicillinase phenotype produced the ␤-lactamase TEM-1. Twenty isolates had the TEM-1 type promoter P3 (30), and only 1 had the TEM-2 type promoter pair Pa and Pb (13) characterized by a C323T substitution. One strain produced the ␤-lactamase SHV-1, and one strain produced the ␤-lactamase CARB-2.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one of the 23 strains presenting a PL penicillinase phenotype produced the ␤-lactamase TEM-1. Twenty isolates had the TEM-1 type promoter P3 (30), and only 1 had the TEM-2 type promoter pair Pa and Pb (13) characterized by a C323T substitution. One strain produced the ␤-lactamase SHV-1, and one strain produced the ␤-lactamase CARB-2.…”
Section: Resultsmentioning
confidence: 99%
“…A pBR322-derived vector, pBREP, was constructed to functionally express the mature form of wild-type rice EPSPS (OsEPSPS; Xu et al, 2002) in E. coli under the control of the bla promoter (Russell and Bennett, 1981). Random mutagenesis via error-prone PCR must be performed on sequences less than 1 kb (Cadwell and Joyce, 1994), thus the OsEPSPS coding sequence was separated into two regions (36-542 bp, 542-1,335 bp) to perform error-prone PCR.…”
Section: Identification Of Osepsps Mutant Conferring Glyphosate Resismentioning
confidence: 99%
“…a Nucieotide position in the Tn3 sequence (16 (4,8,29). The nucleotide sequence differences that we established between Tn2 and Tn3 are shown in Table 1.…”
Section: Hicisf-hoihaimentioning
confidence: 99%
“…(Coordinates established for the nucleotide sequence of Tn3 [16] are used to identify corresponding regions in other Tn3-like transposons.) It was concluded that this mutant transposon, designated Tn2661, carries two overlapping promoters (Pa and Pb) which result in the initiation of two new transcripts, each at a greater efficiency than that from P3, the natural ,B-lactamase promoter used in Tn3, Tn2660, and pBR322 (4,8,29,33 [28] [ Fig. 1]).…”
mentioning
confidence: 99%